Mild Botulism From Illicitly Brewed Alcohol in a Large Prison Outbreak in Mississippi - Marlow, Mariel; Edwards, Leslie; McCrickard, Lindsey; Francois Watkins, Louise K.; Anderson, Jannifer; Hand, Sheryl; Taylor, Kathryn; Dykes, Janet; Byers, Paul; Chatham-Stephens, Kevin (Frontiers in Public Health, 2021)
Botulism is typically described as a rapidly progressing, severe neuroparalytic disease. Foodborne botulism is transmitted through consuming food or drink that has been contaminated with botulinum toxin. During a botulism outbreak linked to illicitly brewed alcohol (also known as “hooch” or “pruno”) in a prison, 11 (35%) of 31 inmates that consumed contaminated hooch had mild illnesses. This includes 2 inmates with laboratory confirmed botulism. The most frequently reported signs and symptoms among the 11 patients with mild illness included dry mouth (91%), hoarse voice (91%), difficulty swallowing (82%), fatigue (82%), and abdominal pain (82%). Foodborne botulism is likely underdiagnosed and underreported in patients with mild illness. Botulism should be considered on the differential diagnosis for patients with cranial nerve palsies.